Stereoselective tetrahydrofuran synthesis - Shaw, Duncan Edward (1993)
This thesis begins in Chapter One with a discussion of the role of electrophilic cyclisation in the synthesis of tetrahydrofurans. Chapter Two begins with a discussion of the synthesis of iodo-olactones, by the iodolactonisation of β-silyloxy-δ-alkenoic acids (Scheme A). It will show how the potential of this chemistry has been expanded by proving the absolute stereochemistry at the iodine centre.